DEVELOPMENT OF TEXTILE FOR ANTI ULTRAVIOLET ROOF THROUGH APPLICATION OF ZnO NANOPARTICLE USING THE MODIFIED PADDING METHOD - Doni Sugiyana; Wulan Septiani; Agus Surya Mulyawan; Tatang Wahyudi (Balai Besar Tekstil, 2018)
Development of textile as a roof with durability against ultraviolet/UV radiation can be achieved through the application of ZnO nanoparticles as UV absorber. Immobilization of ZnO nanoparticles onto cotton roof fabric using modified pad-dry-cure method and evaluation of its durability under ultraviolet irradiation was carried out in this research. Research methods including preparation of ZnO nanoparticles suspension and padding process using pad-dry-cure machine with modification of padding-drying multiplied process cycle up to 2 cycles. Evaluation and testing have been done upon durability of nanoparticles attachment on fabric and tensile strength of fabric after UV irradiation. Homogenous ZnO nanoparticle distribution on fabric surface has been obtained by using PVA concentration of 10%. Rain shower test shows that the fabric treated with modified method has higher water rejection performance than that of fabric treated with conventional method, as well as has good durability of attachment. After 5 hrs of UV irradiation, reduction of tensile strength in fabric treated with modified method were found only 1.2% and 1.5% for warp and weft directions respectively, lower than that of fabric treated with conventional method with 1.4% and 1.7% of respective reduction in warp and weft directions